Metode Pendidikan Akhlak Bagi Anak dalam Perspektif Hadis Nabawi - Muchtar, M. Ilham; Fernandes, Harianto; Sumiati, Sumiati (TARBAWI : Jurnal Pendidikan Agama Islam, 2024)
AbstractMoral education has a central role in shaping the character and behavior of students. In the Islamic context, the moral teachings contained in the hadith of the Prophet Muhammad SAW provide a strong foundation for forming noble morals. This paper aims to present a literature review regarding the Prophet Muhammad's moral education methods contained in the hadith of the prophet in the Book of Sahih Bukhari no. 5376 and 6234. The method of moral education can be understood through a number of hadiths which provide guidance on the behavior and attitudes that should be adopted by Muslims. Based on the two hadiths that are the object of research above, several methods of moral education in the perspective of the prophet's hadith can be put forward that are effective in influencing children's behavior and morals. The methods referred to include the exemplary method, advice method, habituation method and recommendation and threat method. Children's moral education will help in forming strong characters and integrity. This includes values such as honesty, justice, patience, and compassion. In this case, children's moral education in the perspective of Nabawi hadith can be implemented in the four main characters, namely politeness, discipline, honesty, friendship and communicative.